Contribution to improvement of knowledge management in the construction industry - Stakeholders' perspective on implementation in the largest construction companies. Issue 1 (31st December 2022) - Marinho, António Joaquim Coelho; Couto, João
Abstract: Knowledge management (KM) is crucial to ensure that business enterprises effectively leverage existing knowledge within the organization and produce faster and more effective decision-making. This article analyses the importance of KM in the construction industry in Portugal and investigates the perception of experienced professionals on the implementation of KM in this industry, its benefits, and restrictions to its implementation, and how knowledge is obtained and shared. A survey was conducted among experienced professionals working in the largest construction companies in Portugal—administrators, project managers, and budget officers. The validity and reliability of the results were achieved by statistically evaluating the respondents' answers to the variables under study. From the analysis of the results, the relevance of KM is evident, and its greatest benefits are the sharing of information and the exchange of experiences. The lessons learned from completed projects and work meetings are pointed out as the most effective and usual ways to obtain knowledge, but there is a pressing need for a change in mentality to overcome the main barrier to the implementation of KM. This study aims to help construction companies in Portugal to develop strategies to implement KM and knowledge sharing.